2011
DOI: 10.1007/s00167-011-1768-6
|View full text |Cite
|
Sign up to set email alerts
|

Patellar morphology and femoral component geometry influence patellofemoral contact stress in total knee arthroplasty without patellar resurfacing

Abstract: Case control study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Currently, the existing homogenized finite element (hFE) models of patella rely on material laws identified not on the patellar bone, but, for example, femur or vertebra (Fitzpatrick et al, 2011;Ho et al, 2014;Takahashi et al, 2012). Furthermore, the anisotropy of the trabecular bone, shown to be crucial for predicting its elastic properties on various anatomical sites (Maquer et al, 2015), is completely overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the existing homogenized finite element (hFE) models of patella rely on material laws identified not on the patellar bone, but, for example, femur or vertebra (Fitzpatrick et al, 2011;Ho et al, 2014;Takahashi et al, 2012). Furthermore, the anisotropy of the trabecular bone, shown to be crucial for predicting its elastic properties on various anatomical sites (Maquer et al, 2015), is completely overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of each patella was extracted from segmented μCT scans, obtained during a previous study [7] , and imported to Geomagic (Geomagic, Inc., Morrisville, North Carolina, USA) to create non-uniform rational Bspline (NURBS) surfaces. To simulate non-resurfaced cases, we added a cartilage layer for each patella by a uniform extrusion (3 mm) of the posterior articular surface of the patellar bone [6] . To simulate the resurfaced cases, we replicated recommendations of the manufacturer (Symbios, Yverdon-les-Bain, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…However, literature is lacking a validated patellar material law for accurate strain predictions. Currently, the existing patellar numerical homogenized models (hFE) rely on isotropic material laws obtained from other anatomical sites, such as femora or vertebra [3,5,6] In a previous study, we identified and validated a patellar material law based on morphology-elasticity relationship by means * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo (Carpenter et al, 2009;Sharma et al, 2012), in vitro (Lie et al, 2005;Matsuda et al, 1997;Merican et al, 2014) and in silico (Amirouche et al, 2013;Fitzpatrick et al, 2011;Takahashi et al, 2012) studies have shown that TKA leads to significant changes in patellar kinematics, forces acting on the patella, and resulting bone strain in comparison with the intact knee. One of the possible causes of these changes can be related to a surgical technique influencing the positioning of the prosthetic components, their rotation around the joint axes, and the amount of bone cut.…”
Section: Introductionmentioning
confidence: 99%
“…Such knowledge in combination with a patientspecific numerical model would help to improve patellar resection technique during surgery planning. Moreover, all numerical models predicting patellar bone strain assign elastic properties measured on other bones than the patella (Fitzpatrick et al, 2011;Ho et al, 2014;Takahashi et al, 2012) due to the limited number of studies focused on the measuring of patellar mechanical properties.…”
Section: Introductionmentioning
confidence: 99%